Climate and land-use change during the late Holocene at Lake Ledro (southern Alps, Italy). - Joannin, Sébastien; Magny, Michel; Peyron, Odile; Vannière, Boris; Galop, Didier (HoloceneHolocene, 2014)
This paper investigates the relative influences of climatic and anthropogenic factors in explaining environmental and societal changes in the southern Alps, Italy. We investigate a deep sediment core (LL081) from Lake Ledro (652 m a.s.l.). Environmental changes are reconstructed through multiproxy analysis, that is, pollen-based vegetation and climate reconstruction, magnetic susceptibility (MS), lake level, and flood frequency, and the paper focuses on the climate and land-use changes which occurred during the late Holocene. For this time interval, Lake Ledro records high mean water table, increasing amount of pollen-based precipitation, and more erosive conditions. Therefore, while a more humid late Holocene in the southern Alps has the potential to reinforce the forest presence, pollen evidence suggests that anthropogenic activities changed the impact of this regional scenario. Land-use activity (forest clearance for pastoralism, farming, and arboriculture) opened up the large vegetated slopes in the catchment of Lake Ledro, which in turn magnified the erosion related to the change in the precipitation pattern. The record of an almost continuous human occupation for the last 4100 cal. BP is divided into several land-use phases. On the one hand, forest redevelopments on abandoned or less cultivated areas appear to be climatically induced as they occurred in relation with well-known events such as the 2.8-kyr cold event and the ‘Little Ice Age’. On the other hand, climatically independent changes in land use or habitat modes are observed, such as the late-Bronze-Age lake-dwellings abandonment, the human population migration at c. 1600 cal. BP, and the period of the Black Death and famines at 600 cal. BP. [ABSTRACT FROM PUBLISHER]
Keywords: climate oscillations; Land-use; Late Holocene; soil erosion; southern Alps; Vegetation dynamic

The Late Holocene in the western Pyrenees: A critical review of the current situation of palaeopalynological research - Hernández-Beloqui, Begoña; Iriarte-Chiapusso, María-José; Echazarreta-Gallego, Amaya; Ayerdi, Miren (Quaternary International, 2014)
As the vegetation is a social product resulting from the interaction of human beings with the environment, its study contributes towards an understanding of past human cultures. In particular, during the Late Holocene, the socio-cultural evolution of humans has undergone a series of major changes, which have impacted on their environmental setting. In this way, palynological analysis has been able to observe an interesting evolution in anthropization processes since the early Iron Age. However, these observations are conditioned by the volume of deposits that have been studied and their chrono-cultural sequencing. Other factors, such as the deficient preservation of sporo-pollen remains and the lack of well-dated continuous records in non-anthropic deposits, equally restrict our knowledge of the topic. The information available to date confirms that since the first millennium cal BC the vegetation (determining the bio-geographic variety of the territory) has been greatly influenced by human action, on both the Atlantic and the Mediterranean sides of the watershed.
Keywords: Anthropization; Late Holocene; Northern Iberian Peninsula; Palaeopalynology; Vegetation

Vegetation, fire, climate and human disturbance history in the southwestern Mediterranean area during the late Holocene - Jiménez-Moreno, Gonzalo; García-Alix, Antonio; Hernández-Corbalán, María Dolores; Anderson, R. Scott; Delgado-Huertas, Antonio (Quaternary Research, 2012)
Detailed pollen, charcoal, isotope and magnetic susceptibility data from an alpine lake sediment core from Sierra Nevada, southern Spain record changes in vegetation, ﬁre history and lake sedimentation since ca. 4100 cal yr BP. The proxies studied record an arid period from ca. 3800 to 3100 cal yr BP characterized by more xerophytic vegetation and lower lake levels. A humid period is recorded between ca. 3100 and 1850 cal yr BP, which occurred in two steps: (1) an increase in evergreen Quercus between 3100 and 2500 cal yr BP, indicating milder conditions than previously and (2) an increase in deciduous Quercus and higher lake levels, between ca. 2500 and 1850 cal yr BP, indicating a further increase in humidity and reduction in seasonal contrast. Humid maxima occurred during the Roman Humid Period, previously identiﬁed in other studies in the Mediterranean region. Intensiﬁed ﬁre activity at this time could be related to an increase in fuel load and/or in human disturbance. An arid period subsequently occurred between 1850 and 650 cal yr BP, though a decrease in Quercus and an increase in xerophytes. The alternation of persistent North Atlantic Oscillation modes probably played an important role in controlling these humid–arid cycles
The following values have no corresponding Zotero field: publisher: University of Washington
Keywords: climate; Fire history; Late Holocene; Roman Humid Period; Sierra Nevada; southern Spain

A map of autumn precipitation for the third millennium BP in the Eastern Iberian Peninsula from charcoal carbon isotopes - Aguilera, M.; Espinar, C.; Ferrio, J. P.; Pérez, G.; Voltas, J. (Journal of Geochemical Exploration, 2009)
Carbon isotope composition (δ 13 C) in tree-rings has become routinely used in palaeoclimatic research for the assessment of changes in plant water availability in seasonally dry climates. However, the distribution of long tree-ring records around the world is very limited. Alternatively, the original climate signal of wood δ 13 C is well preserved in fossil charcoal and, accordingly, charcoal δ 13 C can be used to quantify past changes in water availability (e.g. precipitation). We report a case study on spatial palaeoclimate reconstruction which aims to characterize the transition between Bronze and Iron Ages, the so-called Iron Age Cold Epoch (ca. 900– 300 BCE), using charcoals of Quercus ilex/coccifera from a set of 11 contemporary archaeological sites of eastern Spain. Climatic inferences were obtained after calibrating a linear model predicting seasonal precipitation from δ 13 C of Q. ilex wood samples obtained across a rainfall gradient. The best regression model corresponded to September–December (autumn) precipitation (Paut ), in agreement with the fact that Q. ilex is able to exploit previous-year water reserves thanks to very effective water uptake. Subsequently, we estimated Paut from the δ 13 C of fossil charcoal to infer spatial patterns in water availability. Overall, estimated past Paut was about 19% higher (296 mm) than present-time values averaged across archaeological sites (249 mm). However, a clear geographic pattern of differences in precipitation could be observed in which the inner continental regions of eastern Spain were characterized by more humid conditions in the past, whereas the coastal strip of the Mediterranean Sea barely differed in past and present Paut values. The quite uniform distribution of archaeological sites over eastern Spain allowed development of contour maps of absolute and relative (to present) past Paut using gridded interpolation methods implemented in a GIS, highlighting the potential of this approach for reconstructing high-resolution spatial patterns of past climate
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Drought; GIS; Iron Age Cold Epoch; Isoscape; Late Holocene; Mediterranean climate; Quercus ilex